Effect Of Augmented Reality-Based Textbook On Geometry Spatial Ability Of Deaf Students: A-B-A SSR - Lia Arum Puspitasari; Sugiman (Riemann: Research of Mathematics and Mathematics Education, 2026)
Mathematical spatial ability plays a crucial role in geometry learning, particularly in visualizing and manipulating three-dimensional objects. However, students with hearing impairment often face difficulties in developing spatial reasoning due to limited access to dynamic and interactive visual learning media, which can hinder their overall performance in geometry and related subjects. Although Augmented Reality (AR) has been widely implemented in mathematics education, empirical evidence on its effectiveness in improving spatial ability among deaf students, particularly using a Single Subject Research (SSR) design, remains limited. This study aims to examine the effect of an AR-based mathematics textbook on the mathematical spatial ability of three deaf students at a special senior high school (SMALB). A mixed-methods embedded design was employed, with quantitative data collected using a Single Subject Research (A1–B–A2) model and qualitative data obtained from observations, interviews, and questionnaires to explore students’ learning experiences. Quantitative data were analyzed using visual and quantitative techniques in a single-subject research design. The findings indicate consistent improvement during the intervention phase, supported by positive trend direction, clear level changes, immediacy of effect, and 0% data overlap between baseline and intervention across subjects. These results provide evidence of the effectiveness of AR-based mathematics textbooks in improving and sustaining mathematical spatial ability within the observed cases of deaf students in geometry learning.